Rigid Cost Structures as a Preemptive Strategy - Artz, Martin; Holzhacker, Martin; Hoppe, André (The Accounting Review, 2026)
ABSTRACT We examine whether firms strategically increase cost rigidity to adopt an aggressive product market stance. Using large cuts in industry-level import tariff rates as a setting, we find that domestic firms respond to a looming competitive threat from foreign rivals by raising cost rigidity. This increase cannot plausibly be explained by investments to create physical excess capacity, suggesting firms enter cost commitments for labor and procurement instead. Additional tests corroborate the hypothesized preemptive intent. First, the increase in cost rigidity is concentrated in industries in which a firm’s aggressive market stance elicits a softening of competition. Second, it is only in these industries that firms with rigid cost structures experience market share gains around a large tariff cut. The latter effect is more pronounced the more reliably firms’ cost structures can be discerned from their financial statements. Overall, our study suggests that firms enter cost commitments as a preemptive strategy. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: L22; M21; M40; M41.